2019
DOI: 10.1093/hwj/dbz009
|View full text |Cite
|
Sign up to set email alerts
|

Oral Histories, Public Engagement and the Making of Positive in Prison

Abstract: How might creative practices surrounding oral history contribute to public engagement and to historical research itself? These questions are considered here through a reflective account of the making of the audio drama Positive in Prison: HIV Stories from a Dublin Jail. Positive in Prison is based on oral histories of HIV/AIDS in the Republic of Ireland, gathered in 2016–17 as part of the Wellcome Trust-funded project ‘Prisons, Medical Care and Entitlement to Health in England and Ireland, 1850–2000’. This pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…18 This practice of segregation in a separate wing or unit was also adopted in the Republic of Ireland and Portugal, and later in Greece, Sweden, and Bulgaria as well. 19 In 1987, only six countries reported no special restrictions at all on the accommodation, movement, or activities of prisoners with HIV/ AIDS: Austria, Denmark, France, Italy, Spain, and Switzerland. 20 It is notable that these decisions to implement special restrictions or separate units were often driven by direct action in various forms.…”
Section: International Recommendations and Their Implementationmentioning
confidence: 99%
“…18 This practice of segregation in a separate wing or unit was also adopted in the Republic of Ireland and Portugal, and later in Greece, Sweden, and Bulgaria as well. 19 In 1987, only six countries reported no special restrictions at all on the accommodation, movement, or activities of prisoners with HIV/ AIDS: Austria, Denmark, France, Italy, Spain, and Switzerland. 20 It is notable that these decisions to implement special restrictions or separate units were often driven by direct action in various forms.…”
Section: International Recommendations and Their Implementationmentioning
confidence: 99%
“…However, arts-based engagement approaches can also be used to provide insights of relevance for the research itself and how it evolves, for example, to help provide new interpretations of research data that can help in sense-making [17,39]. To illustrate, a research project examining how to translate women's experiences of responses to their safety concerns in pregnancy into useful health information used insights gained from participants in the development of a health information resource for pregnant women to evolve the scope of the research study [40].…”
Section: What Does the Use Of Artsbased Engagement Approaches Seek To...mentioning
confidence: 99%
“…An example of this type of missed opportunity can also be found in the literature. For example, Weston (2019) notes that a playwright she worked with to translate her interview-based research on the impact of HIV/AIDS in a prison in Dublin, Ireland, into an audio drama highlighted gaps in the underlying research study [39]. Through her thorough review of the interview transcripts, the playwright observed a complete absence of former prisoners amongst the interviewees.…”
Section: What Does the Use Of Artsbased Engagement Approaches Seek To...mentioning
confidence: 99%
See 2 more Smart Citations